Role of Political Environment on Content Editing in Kurdish Satellite Channels: Descriptive Research (Raparin Journal of Humanities (RJH), 2023)
This research in time with the wide range of the democracy and ethics duty spreads in KRG Television station out any requires on the journalist's, day after day everything gets change, but the action will request more awareness of how to collect and editing the information and how to broadcast it. the objectives of this research relate to a warning about how the media content influences the political environment on the KRG satellite Channels. For this reason, this research depends on the survey methodology, a survey to find out the opinions of all academic experts in the field of public university media departments in the Kurdistan Region-Iraq, duration from February, 2 till May 4, 2022. The characteristics of the research think that all media channels and journalists can’t consist of professional skills (values, measurements). On the other hand, the researchers come to the conclusion that the political environment affected the media content, as. At the same time, besides the demography of the research, there are no differences in measurements that will reveal the positive direction.